The effectiveness of safety and security at shopping malls / Mohd Haris Mustafar - Mustafar, Mohd Haris (Faculty of Architecture, Planning and Surveying, 2009)
A shopping mall is a place that contains a variety of goods, services, food and etc. however, this place must be maintained and controlled in terms of health and safety so that all residents are safe and comfortable. With the safety and security in shopping malls, harmony in the supermarket is more secure. However, the effectiveness and efficiency of security system and safety is dependent on the quality of service and functionality. The safety and security system in shopping malls such as closed circuit television (CCTV), emergency alarm, hose reel, emergency lighting and so on. For this study is the effectiveness of safety and security at the shopping malls. Safety and security system in the shopping malls are very important and should be systematically manage. Effectiveness of a security system depends on the high quality of services and also on management. Department that involved in the safety and security in this building are security and maintenance department. This department is responsible for all problems that occur in this building. However, residents should also be constantly vigilant about the safety of themselves and their property, not only depend on management entirely.